Awareness and Utilization of Stress Management Interventions among Health care Professionals in Nnamdi Azikiwe University, Awka - Igwilo, Sabina; Obiekwe, Mercy (Athena: Physical Education and Sports Journal, 2025)
The aim of this study was to explore the awareness and Utilization of Stress Management Interventions among Health care Professionals in Nnamdi Azikiwe University Awka. Four research questions guided the study and a descriptive survey research design adopted for the study. The population of the study consisted of 156 health participants and the whole population was used. The finding of the study reveal that the health care Professionals of Nnamdi Azikiwe University, Awka are aware of stress Management Interventions techniques but they lack time and scheduling constraints in utilizing the techniques. It was recommended among others that the institution should establish a student -led club for health professionals to meet regularly to practice stress Management Interventions techniques led by experience instructors or mental health professionals.